Bienestar Subjetivo y su relación con la percepción del contexto escolar en adolescentes de cinco municipios del departamento del Tolima (2020)
This project has been carried out considering the concepts of subjective well-being and the perception of the school context. The sample consisted of 1305 young people between the ages of 11 and 20, students from different schools in five municipalities in the department of Tolima (Armero, Ibagué, Líbano, Ortega, Prado), five quantitative tests were applied: Questionnaire on skills and difficulties, Scale of life satisfaction, scale of positive and negative experiences, scale of measurement of different aspects of the school context and the subjective well-being index. These instruments allowed to answer the following objective: Analyze the existing relationship between subjective well-being and the perception with the school context, which allowed to conclude that there is a positive relationship between the perception of the school context and well-being. As difficulties arise regarding teachers or subjects at school, satisfaction with life, satisfaction with domains and mental health decrease.